Subsídios do Geoprocessamento na Agricultura de Precisão - SANTOS, Agatha Pereira dos (2025)
For a long time farmers have been farming without adequate tools to enable more efficient management of agricultural crops. Thus, it is characterized by low productivity, dependent on the physical-natural characteristics of the environment, including presence or not of pests and means to combat them. On the other hand, the emergence of geoprocessing techniques allowed more precise exercise of agriculture, through the storage and processing of data and information collected through the use of a technological system that enables a greater degree of assertiveness for the sector. In this sense, the objective of this work is to analyze the tools and geotechnology techniques applied in Precision Agriculture. Thus, the methodology applied was literature search in the construction of qualitative analysis of precision agriculture showing a modern approach in agricultural management that uses advanced technologies to optimize production and increase efficiency. The results demonstrate that, in precision agriculture, geoprocessing plays a crucial role by providing subsidies for efficient and sustainable management of agricultural activities. Precision Agriculture uses the analysis of information in the inter and intra-crop stages, taking into account aspects related to soil variability and climate in agronomic activities. Thus, it is through geoprocessing techniques that the information about the georeferenced areas are verified so that the appropriate process of agricultural automation can be realized promoting the success of the sector.